Phytochemical and biological activities of ethanolic extract of C. hirsuta leaves (Bangladesh Journal of Scientific and Industrial Research, 2013)
This study investigated the phytochemical and biological activities like antioxidant, antibacterial and cytotoxitc effects of C. hirsuta (Synonym- Senna hirsuta) leaf extracted with exhanol. Qualitative phytochemical analyses were accomplished by established methods. Antioxidant, antibacterial and cytotoxic effects were, respectively, measured by DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging method, disc diffusion method and brine shrimp lethality bioassay. The presence of alkaloids, glycosides, anthraquinone glycosides and flavonoids were detected in the leaf extract. The extract showed significant (p < 0.01) radical scavenging effect (IC50, 200.96 ± 0.85 ?g/ml) in comparison to ascorbic acid (IC50, 1.24 ± 0.08 ?g/ml). The extract also showed significant (p < 0.05) zone of inhibitions against Gram-positive Bacillus cereus (13 ± 1.05 mm) and Bacillus megaterium (9 ± 0.85 mm), and Gram-negative Vibrio cholera (20 ± 0.68 mm), Escherichia coli (8 ± 0.92 mm), Pseudomonas aeroginosa (15 ± 1.03 mm), Salmonella paratyphi (9 ± 0.79 mm) and Shigella dysenteriae (8 ± 0.88 mm). In cytotoxic assay, the extract showed the LC50 value 315.5 ?g/ml which was statistically significant (p < 0.01) compared to reference cytotoxic agent vincristine sulfate (LC50, 38.99 ?g/ml). DOI: http://dx.doi.org/10.3329/bjsir.v48i1.15413 Bangladesh J. Sci. Ind. Res. 48(1), 43-50, 2013